Trilogues in Council: disrupting the diplomatic culture?. Issue 1 (2nd January 2021) - Brandsma, Gijs Jan; Dionigi, Maja K.; Greenwood, Justin; Roederer-Rynning, Christilla
ABSTRACT: This article explores the institutionalization of trilogues in the Council. What kind of practices have emerged in the Council to underpin this body's participation in trilogues, and how do these shape the decision-making culture in the Council? We conceptualize the institutionalization of trilogues in the Council using delegation theory, and particularly through the lens of two ideal-types of delegation focusing on sanctions and selection, respectively. We explore these ideal-types by drawing on extensive elite interviews. Following the distinction between mandating, monitoring, and sanctioning common to delegation relationships, we find the greatest changes in the mandating and monitoring of the Presidency, and few changes in the sanctioning processes. This shows that the sanctions model is on the rise. We find that trilogues have changed the Council as a legislative institution.